The impact of higher education investment on the urban-rural income gap: An analysis of mediating and threshold effects based on data from China's eight major comprehensive economic zones. - Shuyao Liu; Yan Zhang; Yanbo Liu; Ning Wang (PLoS ONE, 2025)
Background Since the reform and opening up, China's urban and rural economic development has exhibited characteristics of imbalance, with the urban-rural income gap being the largest and most noticeable issue facing China's socio-economic landscape. Alleviating and effectively resolving the urban-rural income disparity is crucial for achieving overall common prosperity. Therefore, this study provides insights for strategically narrowing the urban-rural income gap from the perspective of higher education investment. Methods We employ a panel fixed effects model to examine the basic regression, heterogeneity, mediating effects, and threshold effects. Simultaneously, we address the endogeneity issues in basic regression and mediating effects using the instrumental variable method. Additionally, we adopt the substitution of variables to ensure the robustness of the results. Results This paper selects panel data from China's eight major comprehensive economic zones from 2003 to 2021 for analysis. The findings reveal that, overall, higher education investment in China's eight major comprehensive economic zones can narrow the urban-rural income gap. Specifically, higher education investment in 50% of these comprehensive economic zones-namely, the Northern Coastal Comprehensive Economic Zone, Eastern Coastal Comprehensive Economic Zone, Northeast Comprehensive Economic Zone, and Middle Yangtze River Comprehensive Economic Zone-can reduce the urban-rural income disparity. Conversely, higher education investment in the Middle Yellow River Comprehensive Economic Zone, Southern Coastal Comprehensive Economic Zone, Greater Southwest Comprehensive Economic Zone, and Greater Northwest Comprehensive Economic Zone has widened the urban-rural income gap. Additionally, higher education investment can affect the urban-rural income disparity through technological innovation. Overall, the impact of higher education investment on the urban-rural income gap in China's eight major comprehensive economic zones is also influenced by the level of economic development, exhibiting an "inverted U-shaped" characteristic. This nonlinear impact varies across regions. Conclusions In conclusion, to narrow the urban-rural income gap across China's eight major integrated economic zones, it is necessary to improve the mechanism for higher education investment in these zones. Strategies should be based on regional differences, tailored to local conditions, and implemented with a differentiated and precise approach to higher education development across regions. Emphasis should also be placed on the research and application of innovative technologies to achieve deep integration between urban and rural areas within China's eight major integrated economic zones.